New Trends in Geomatics, in the Era of Lowcost Sensors, Free and Open Source Software and HPC GeoBigData infrastructures - Ravanelli, Roberta; Di Rita, Martina; Belloni, Valeria; Nascetti, Andrea; Mazzoni, Augusto; Crespi, Mattia (GEOmedia, 2017)
Nowadays, the increasing availability of low-cost sensors, Free and Open Source Software and High Performance Computing infrastructures allows Geomatics to widen its application scope, by stimulating new challenging investigations related to the modeling of the observations provided by these new tools. In this review, some methodologies and applications, developed at the Geodesy and Geomatics Division (DICEA) of University of Rome "La Sapienza”, are shortly presented. Directly related to the mentioned software and hardware new availability, they are already ready for industrial applications and hopefully can broaden the interaction between Geomatics and other scientific and technological disciplines.